Can ethical leaders drive employees' CSR engagement?. Issue 5 (17th July 2019) - Nejati, Mehran; Salamzadeh, Yashar; Loke, Cheng Kong
Abstract : Purpose: The association between ethical leadership and employees' ethical behaviors is well-established. But can ethical leadership go beyond this and drive employees' corporate social responsibility (CSR) engagement? The purpose of this study is to examine the association between ethical leadership and employees' perception of their engagement in CSR activities while exploring the mediating role of person–organization fit. Design/methodology/approach: Using a quantitative research design, data were collected via self-administered questionnaires from 142 employees of multi-national companies in Malaysia. This study used partial-least squares structural equation modeling to test and validate the research model and hypotheses posited. Findings: The results reveal that ethical leadership has a positive impact on employees' CSR engagement, mediated through person–organization fit. Moreover, analyses were carried out to assess the predictive performance of the proposed model. Our results confirmed the predictive capability of the proposed model. Research limitations/implications: This study has provided a better understanding of employees' CSR engagement, which is a crucial factor for effectiveness of CSR implementation in any organization. Finding evidence on the positive role of ethical leadership in driving employees' CSR engagement extends both the leadership and CSR literature and offers new avenues for future research studies. Practical implications: This study has shown that ethical leadership can stimulate employees' CSR engagement through creating a better person–organization fit. This understanding can help managers in finding ways for more effective involvement of employees in a company's CSR activities and creating a better working environment. Social implications: Organizations can find better ways to involve employees in CSR activities through having ethical leaders who lead by example and champion social causes. Although ethical leadership will benefit society, it will also help employees experience a better fit between their values and those of the organization. Originality/value: Despite extensive research on CSR, its drivers and outcomes, there is still limited knowledge on the role of leaders in driving employees' CSR engagement. Findings from an emerging economy (i.e. Malaysia) will offer fresh insights into the growing CSR and leadership literature.